Odnos večinskega prebivalstva do priseljenskih skupnosti - Mandelc, Damjan (Teorija in praksa, 2022)
The article examines the ways the majority population of Celje, Slovenia’s third-biggest city, view the Albanian immigrant community, one that which has recently grown in size and is being met with a negative attitude and ethnic distance from the majority population. Based on theoretical assumptions in the fields of sociology and migration studies, a research plan of mixed methods was designed. Analysis of the results demonstrated that the majority of the population mainly held a negative attitude, while partial correlation was observed with the assumptions made in the theoretical starting points, namely, that female respondents with a higher education and higher income hold slightly more favourable attitudes to immigrants than males with a lower education and lower income
Keywords: Albanski izseljenci; alfanofobija; Družbene vrednote; ksenofobija; Mestna občina Celje; odnos do albancev; odnos do albanskih priselnjencev; odnos do priseljencev; Priseljenci; Stališče (psihologija)